Positioning Map: a Visual Technique to Improve the Layout of Diagram Contextual Information - Genon, Nicolas; Matulevicius, Raimundas; Englebert, Vincent; Heymans, Patrick (Electronic Communications of the EASST, 2008)
The presentation of information is a difficult activity. It requires to deal with model complexity, characterised among other things by the number of visualelements per diagram. In this position paper, we propose a positioning map constructed by combining the navigation and locator maps – two techniques resulting from the theoretical principles of effective communication. We believe that the positioning map is a better means than navigation and locator maps together to decompose models and to integrate their information cognitively. However, we still need to validate our proposal through empirical studies.